THU0163 Early Response as A Predictor of Long-Term Clinical Response in DMARD-Naïve Patients with Severe, Active and Progressive RA Treated with Certolizumab Pegol plus Optimized MTX versus Optimized MTX Alone. (15th July 2016) - Mariette, X.; Bingham, C.; Burmester, G.-R.; Bykerk, V.P.; Emery, P.; Furst, D.; van der Heijde, D.; van Vollenhoven, R.; VanLunen, B.; Arendt, C.; Weinblatt, M.
Abstract : Background: C-EARLY (NCT01519791 ) assessed the efficacy and safety of certolizumab pegol (CZP)+optimized MTX vs placebo (PBO)+optimized MTX in inducing and maintaining a sustained clinical response, and inhibiting radiographic damage, in DMARD-naïve patients (pts) with active, severe, progressive RA. 1 Here, we examine the association between an inadequate response to PBO+MTX or CZP+MTX treatments at Week (Wk) 12 (lack of improvement from baseline [BL] in DAS28[ESR], DAS28[CRP] or CDAI) and corresponding response at Wk 52. Objectives: To examine the association between Wk12 response and Wk52 clinical response (remission [REM]/low disease activity [LDA]) in recently diagnosed DMARD-naïve pts with active, severe, progressive RA, treated with CZP+optimized MTX vs PBO+optimized MTX. Methods: This multicenter, double-blind, randomized controlled trial enrolled pts who were DMARD-naïve with active, severe, progressive RA (<1yr since diagnosis, fulfilling 2010 ACR/EULAR criteria). 879 pts were randomized 3:1 to CZP (200mg Q2W+MTX; n=660) or PBO Q2W+MTX (n=219). MTX was initiated at 10mg/wk and increased to 25mg/wk by Wk8; maximum tolerated dose per pt (mean optimized dose, CZP: 21mg/wk, PBO: 22mg/wk) was maintained to Wk52. Negative predictive values (NPV) were defined as probability of failing to achieve Wk52 REM (DAS28[ESR]/[CRP]<2.6 or CDAI≤2.8) or LDA (DAS28[ESR]/[CRP]≤3.2 or CDAI≤10) after failing to achieve a corresponding defined response at Wk12; change from BL in DAS28(ESR)/(CRP)≥0.6 or ≥1.2/CDAI≥6 and ≥12. DAS28(CRP) LDA/REM definitions are not validated. Observed data were utilized for Wk12 responses; missing Wk52 values were imputed using non-responder imputation. Results: The NPV of Wk12 responses were high (Table ): PBO+MTX pts who did not achieve DAS28(ESR) improvements from BL ≥0.6 had 94% probability of not being in REM or LDA at Wk52. CZP+MTX pts who did not achieve DAS28(ESR) improvements from BL ≥1.2 had 93% probability of not being in REM at Wk52. NPV of changes in DAS28(CRP) and CDAI at Wk12 were less informative for predicting remission at 1yr (Table ). Conclusions: In early RA pts treated with optimized-dose MTX, failure to achieve a ≥0.6 DAS28(ESR) reduction from BL at Wk12 was associated with a low probability (6%) of DAS28(ESR) REM/LDA at Wk52, supporting treatment step-up at 3 months. For pts with active, severe RA with poor prognostic factors where CZP has been initiated as first-line treatment, failure to achieve a rapid decrease of 1.2 points was associated with a reduced likelihood of achieving REM (7%). These findings in DMARD-naïve pts are consistent with the negative predictability outcomes for CZP in established RA. 2 References: Weinblatt M. Arthritis Rheumatol 2015;67(S10); van der Heijde D. J Rheumatol 2012;39:1326–33 Acknowledgement: The authors acknowledge Costello Medical Consulting, funded by UCB Pharma, for writing and editorial assistance. Disclosure of Interest: X. Mariette Grant/research support from: Pfizer and GlaxoSmithKline., Consultant for: Bristol-Myers Squibb, GlaxoSmithKline, Pfizer, UCB Pharma and Sanofi-Aventis, C. Bingham Consultant for: UCB Pharma, G.-R. Burmester Consultant for: AbbVie, MSD, Pfizer, Roche and UCB Pharma, V. Bykerk: None declared, P. Emery Consultant for: Bristol-Myers Squibb, Pfizer, MSD, AbbVie, UCB Pharma, Roche, Schering Plough, Novartis and Samsung, D. Furst Grant/research support from: Abbott, Actelion, Amgen, Bristol-Myers Squibb, Gilead, GlaxoSmithKline, NIH, Novartis, Pfizer, Roche/Genentech and UCB Pharma, Consultant for: Abbott, Actelion, Amgen, Bristol-Myers Squibb, Biogen IDEC, Janssen, Gilead, GlaxoSmithKline, NIH, Novartis, Pfizer, Roche/Genentech and UCB Pharma, D. van der Heijde Grant/research support from: AbbVie, Amgen, AstraZeneca, Augurex, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GlaxoSmithKline, Janssen, Merck, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB Pharma and Vertex, Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GlaxoSmithKline, Janssen, Merck, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, UCB Pharma and Vertex, Employee of: Director of Imaging at Rheumatology BV, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, Pfizer, Roche, UCB Pharma, Consultant for: AbbVie, Biotest, BMS, GSK, Janssen, Lilly, Merck, Pfizer, Roche, UCB Pharma, Vertex, B. VanLunen Employee of: UCB Pharma, C. Arendt Employee of: UCB Pharma, M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo Bioscience and UCB Pharma, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Crescendo Bioscience, Lilly, MedImmune, Merck, Novartis, Pfizer, Roche and UCB Pharma